The Trans-Nemunas Region and its Development during Historical Times based on Archaeological Data - Babušytė, Irma (Vilnius University Open Series, 2021)
The lack of archaeological data in Trans-Nemunas region is a huge problem for archaeologists to this day. There are some hillforts, settlements, former village sites extant but most of the burial sites are already gone or destroyed due to agricultural work. Even less of these sites are researched. Therefore, it is difficult to know and understand Trans-Nemunas region development based on archaeological data. The main aim of this article is to sort out when the Prehisotrical times in this region ended, and when the Historical times began, what happened during this time in the territory, while speaking about it‘s accommodation difference. Article contains various theories of historians, archaeologists and linguists about region‘s development during 13th-16th centuries, also the archaeological data was taken from Register of Cultural Property. Based on historians‘ (D. Baronas, A. Dubonis, J. Kiaupienė, R. Petrauskas) opinion, the prehistorical times in Trans-Nemunas ends within 13th century‘s end, during great migration to other historical lands of Lithuania and the wars with the Crusaders. During 14th century the lands of Trans-Nemunas region were abandoned, and then residents came back (or newly settled) in the region in the 15th century. Archaeological data confirms these theories. Hillforts became abandoned in the 13th century, and the new settlements, manors and villages appeared only from 15th century.
Keywords: archaeological data; development of settlement; historical development; historical times